Application of Active Targeting Nanoparticles Delivery System for Drugs and Herbal Medicines with Anticancer Activities: A Systematic Review - Nadda Muhamad; Tullayakorn Plengsuriyakarn; Kesara Na-Bangchang (Challenges and Advances in Pharmaceutical Research Vol. 3, 2022)
Due to the non-selective impact of chemotherapeutic medicines on normal cells, patients receiving traditional cancer treatment experience side effects. Drug selectivity in cancer cells is improved by active targeting nanoparticles that are coupled to targeting ligands on the surface of nanoparticles. The objective of the current systematic review was to summarize reports on the selective delivery of drugs herbal medicines with anticancer activities to cancer cells by active targeting nanoparticles. The literature search was conducted through PubMed database search up to March 2017 using the terms nanoparticle, chemotherapy, traditional medicine, herbal medicine, natural medicine, a natural compound, cancer treatment, and active targeting. Based on the predefined inclusion and exclusion criteria, 61 articles out of 695 were included in the analysis. Proteins/peptides, hyaluronic acid, folic acid, antibodies/antibody fragments, aptamer, and carbohydrates/polysaccharides were among the targeted ligands. In vitro and in vivo studies imply that active targeting nanoparticles improve treatment efficacy and safety by increasing selectivity in cellular uptake and/or cytotoxicity over traditional chemotherapeutic medicines and non-targeted nanoparticle platforms. Clinical investigations, on the other hand, are needed to confirm these findings.